ANALYSIS OF HUMOR LANGUAGE TECHNIQUES FROM MALE AND FEMALE PARTICIPANTS IN THE KOMPAS TV STAND UP COMEDY COMPETITION - Rini Indah Sulistyowati; Ganda Januarta; Sofyan Danu Setyadi (Universitas PGRI Palembang, 2024)
Stand Up Comedy Kompas TV is the first single comedy competition event pioneered by Indonesian celebrities, namely Pandji Pragiwaksono, Raditya Dika, Indro Warkop, and Indra Yudhistira, one of the producers and directors of comedy programs at Kompas TV. Not just any comic can appear in this competition (show). The selected comics are the result of selection by the judges so that they can be categorized as the best finalists who of course have undoubted abilities. Stand Up Comedy Kompas TV has broadcast 10 seasons. Uniquely, male participants dominate over female participants. This certainly didn't happen accidentally. Several relevant studies have not raised gender issues in the humorous language techniques of Stand Up Comedy. The aim of this research is to describe the differences in humorous language techniques of male and female participants in the Kompas TV Stand Up Comedy competition. By combining the theories of Berger (1998) and Wijana (2001) with the pragmatic matching method, it is hoped that differences in the humor techniques of male and female participants in the competition can be found. The results showed that the humorous language techniques of male participants that were not used by female participants were (1) infantilism, (2) sexual allusion, (3) repetition, (4) repartee, (5) narcissism, (6) homonyms, ( 7) taboo words, (8) paradoxical figures of speech, (9) exchange of speaking styles, (10) greeting words, and (11) mispronunciations. The female participants' humorous language techniques that were not used by male participants during the audition were (1) role playing, (3) ridicule, (3) roasting, (4) changing words, (5) collocations, and (6) clarification. . From the findings of the use of absurd stories by comic artists, it can be said that the male participants' ability to tell stories outside of logic seems to dominate with the use of this technique by 5 out of 10 male participants in auditioning for SUCI. The language technique of self-deprecation seems to be dominantly used by female comics compared to other humorous language techniques because of the 8 female participants, there are 4 comics who use it.